2003
DOI: 10.1161/01.cir.0000091081.19465.f1
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Assessment of Late Conduction Recurrence Across Radiofrequency Lesions Producing Electrical Disconnection at the Pulmonary Vein Ostium in Patients With Atrial Fibrillation

Abstract: Background-In patients with atrial fibrillation (AF) undergoing radiofrequency (RF) electrical disconnection of multiple pulmonary veins (PVs), the incidence of late conduction recurrences has not been systematically determined. Methods and Results-Using a prospectively designed, multistep approach, we aimed at assessing the correlation between acute achievement and chronic maintenance of electrical conduction block across RF lesions disconnecting the distal tract of the PV in 43 patients (52.3Ϯ8.2 years) with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
298
1
5

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 378 publications
(316 citation statements)
references
References 16 publications
12
298
1
5
Order By: Relevance
“…4,5 Cheema et al 17 showed recurrence of PV conduction in >90% of patients 1 hour after initial electrical isolation. Cappato et al 4 demonstrated that late conduction recurrence across acutely disconnecting RF lesions delivered at the ostia of the multiple PVs is a common finding in patients undergoing catheter ablation of AF.…”
Section: Pv Reconnection and Recurrent Atrial Tachyarrhythmiasmentioning
confidence: 99%
See 3 more Smart Citations
“…4,5 Cheema et al 17 showed recurrence of PV conduction in >90% of patients 1 hour after initial electrical isolation. Cappato et al 4 demonstrated that late conduction recurrence across acutely disconnecting RF lesions delivered at the ostia of the multiple PVs is a common finding in patients undergoing catheter ablation of AF.…”
Section: Pv Reconnection and Recurrent Atrial Tachyarrhythmiasmentioning
confidence: 99%
“…4,5 Cheema et al 17 showed recurrence of PV conduction in >90% of patients 1 hour after initial electrical isolation. Cappato et al 4 demonstrated that late conduction recurrence across acutely disconnecting RF lesions delivered at the ostia of the multiple PVs is a common finding in patients undergoing catheter ablation of AF. Recently, Kowalski demonstrated that PVs showing electrical reconnection after catheter-based antral ablation frequently reveal anatomic gaps or nontransmural lesions at the sites of catheter ablation, and that return of PV conduction after catheter-based isolation procedures is assumed to be attributable to failure to create permanent contiguous transmural lesions in at least part of the ablation line by histological study.…”
Section: Pv Reconnection and Recurrent Atrial Tachyarrhythmiasmentioning
confidence: 99%
See 2 more Smart Citations
“…This is highlighted by the observation that >90 % of patients requiring a second catheter ablation procedure demonstrate one (or more) PV reconnections (see Figure 1A). 26,45 For patients with more advanced forms of AF, recurrences may be due to the persistence of LA substrate abnormality as well as non-PV triggers (see Figure 1B). These triggers can be found in about 50 % of patients and originate in the superior vena cava, left atrial free wall or appendage, coronary sinus, crista terminalis or right atrial free wall.…”
Section: Mechanism Of Atrial Fibrillation Recurrence After Ablationmentioning
confidence: 99%